Nadużycie pozycji dominującej na rynkach nowych technologii w prawie Unii Europejskiej — problemy teoretyczne i praktyczne - Dąbrowski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The paper indicates the current theoretical and practical problems in the application of EU competition policy, especially with respect to the proceedings relating to recognition of an abuse of a dominant position in the new technology market. A brief analysis of the recent Commission’s decisions and Court of Justice’s rulings leads to the conclusion that too often an action that is supposedto enhance the conditions of a free internal market based on competition and consumer’s welfare contradicts those fundamental purposes. Aggressive approach of the EU institutions in the process of interpretation and applying the law causes the entrepreneurs to feel insecure about their investments in the knowledge economy, innovations and increasing market standards, which means so much in this particular branch.
Keywords: Unia Europejska; prawo; nowe technologie; rynki